PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF DALAM BIDANG PENDIDIKAN KHUSUS (Eduscotech, 2024)
This study aims to develop interactive learning media in the field of special education that are feasible and effective in supporting the learning process of students with special needs. The study was conducted in response to the limited availability of learning media that are adaptive to students’ characteristics in special education settings. A Research and Development (R&D) approach was employed using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects included special education teachers and students with special needs. Data were collected through observation, interviews, questionnaires, and documentation. The results indicated that the developed interactive learning media met the feasibility criteria based on validation by content experts, media experts, and special education experts. Limited trials also demonstrated positive responses from both teachers and students, as well as improvements in learning motivation, engagement, and conceptual understanding. Therefore, the interactive learning media developed can be used as an effective alternative to support the learning process in special education.